The role of cardiotrophin-1 in chronic heart failure - L. R. Pakhnova; O. A. Bashkina; L. P. Voronina (Медицинский вестник Юга России, 2023)
An analysis of the literature data on the role of the cardiotrophin-1 protein in chronic heart failure was carried out. Articles were selected and analyzed in PubMed, ScienceDirect, ProQuest, GoogleScholar, Cochrane, Medline, AMED, EMBASE, CINHAL, SportDiscus, Scopus and PEDro databases. The search for articles was carried out using the keywords: «Heart failure», «Biological markers», «Cardiotrophin-1», «Galectin-3», «Myocardium» and their combinations. Inclusion criteria were publication date from 2017 to 2022, clinical studies, meta-analyses and systematic reviews, randomized controlled trials, availability of the full text in the public domain or the abstract. Exclusion criteria: abstracts, monographs, textbooks, publication date before 2017, inconsistency with the research topic. A total of 80 publications were found. The review included 18 publications from 2017 to 2022 that corresponded to the topic and purpose of the study and were significant for revealing the subject of the study. Information is presented on the role of cardiotrophin-1 in chronic heart failure. Cardiotrophin-1 is activated in cardiac fibroblasts and cardiomyocytes in response to mechanical, humoral, metabolic and hypoxic stress. This biomarker is abundantly expressed in cardiac tissue and its overexpression is mainly stimulated by ventricular stretch/pressure, which promotes myocardial hypertrophy. Experimental administration of cardiotrophin-1 leads to fibrosis and myocardial remodeling, which indicates its role as a diagnostic biomarker in these pathologies and chronic heart failure in general.